PMM.17 Proteinuria and Maternal/Fetal Outcomes in Women with Alport's Syndrome and Thin Basement Membrane Nephropathy. (9th June 2014) - Kapoor, D; Hall, M; Ferraro, A; Wallace, S
Abstract : Introduction: We observed that some women with glomerular collagen disorders (Alport's syndrome (AS) or thin basement membrane (TBM) disease) had particularly pronounced increase in proteinuria during pregnancy. Disease-specific pregnancy outcomes for women with AS/TBM are not well reported. The aim of the analysis is to test the hypothesis that these conditions lead to more pronounced increase in proteinuria than other chronic kidney diseases (CKD) and to compare the maternal/fetal outcomes. Methods: 7 patients with AS/TBM, 7 patients with other glomerular diseases and 7 patients with non-glomerular CKD were identified from the Nottingham Obstetric-Renal service over a 2 year period. Outcomes assessed were: increasing proteinuria (protein:creatinine ratios; P:CR), pre-eclampsia, prematurity and small for gestational age (SGA) infants (<10th centile). Results: Baseline proteinuria was similar in women with AS/TBM and other glomerular diseases (238 ± 161 vs. 103 ± 109 mg/mmol, p = 0.14) and higher than in those with non-glomerular diseases (9.6 ± 0.8 mg/mmol, p = 0.005). The increase in proteinuria during pregnancy was greater for women with AS/TBM than for women with other glomerular diseases (4.9 ± 3.6 vs. 1.3 ± 0.8, p = 0.04) and non-glomerular diseases (1.6 ± 1.6, p = 0.05). Nephrotic range proteinuria (P:CR > 300 mg/mmol) during pregnancy was found in 6(86%) women with AS/TBM, 2(29%) women with other glomerular diseases and no women with non-glomerular diseases. In AS/TBM, pre-eclampsia (28.5%), prematurity (14.2%), and SGA(14.2%) rates were similar to those in women with other CKD. Conclusion: Women with AS/TBM are at high relative and absolute risk of pronounced increase in proteinuria during pregnancy. They should be counselled that this may occur and that prophylactic low molecular weight heparin may be indicated to minimise venous thromboembolic events.